Our clinical experience in iatrogenic and traumatic bile duct injury: A retrospective analysis (Annals of Medical Research, 2021)
None
Keywords: Bile Duct Injury; Iatrogenic; Cholecystectomy; Trauma; Hepaticojejunostomy.